Vitamin C Levels in Different Organs of Bat Species from Different Food Groups - Diego Antonio Mena Canata; Mara Silveira Benfato; Francielly Dias Pereira; María João Ramos Pereira; Pabulo Henrique Rampelotto (Life, 2022)
Unlike most animals, most bats cannot synthesize vitamin C endogenously. Consequently, this vitamin must be obtained from the diet. Among the bat species, there are several food groups, such as frugivorous, nectarivorous, insectivorous, and hematophagous. In this work, we measured and compared vitamin C levels in different organs of four species of bats, all collected in southern Brazil. When analyzing and comparing the levels of vitamin C in the four bat species, (regardless of the organ), no significant differences were observed. However, when analyzing and comparing the levels of vitamin C in the four organs (regardless of the species), significant differences were observed, with the highest concentrations in the heart, followed by the liver and brain, while the lowest concentration was measured in the kidneys. Additional differences in the levels of Vitamin C were only observed when each organ was analyzed according to the species/diet. These results indicate a high degree of metabolic homeostasis in bats despite the marked difference in the type of diet.